Aromatherapy massage for you : the practical step-by-step guide to aromatherapy massage at home - Harding, Jennie (Duncan Baird Publishers, 2005)
A practical manual which shows how to use aromatic massage techniques effectively on yourself, friends or family! Includes clear step-by- step instructions on all the basic massage strokes, as well as an in-depth directory of essential oils.